Analysis of genetic aberrations in pediatric high-grade gliomas - M. A. Zaytseva; A. P. Shekhtman; L. I. Papusha; E. F. Valiakhmetova; L. A. Yasko; A. E. Druy (Успехи молекулярной онкологии)
Background. High-grade gliomas are characterized by a wide range of genetic abnormalities. The heterogeneous genomic landscape of pediatric high-grade gliomas allows identifying distinct subgroups of the disease in children and young adults. Most importantly, these subgroups differ by clinical course and prognosis, as well as treatment response to standard therapy.Objective: to assess the profile of molecular genetic markers of high-grade gliomas in children.Materials and methods. In the current study, we examine the frequency of H3F3A, Hist1H3B, BRAF, IDH1 / 2 mutations, the copy number alterations of CDKN2A / 2B genes and the expression of ETV6‑NTRK3 fusion gene in a cohort of 53 pediatric high-grade gliomas.Results. Driver mutations and CDKN2A / 2B deletions were observed in 24 (45 %) and 15 (28 %) of 53 tumors, respectively. Overall, the studied high-grade gliomas harbored 41 genetic aberrations including 24 (58.5 %) somatic missense mutations, 1 (2.4 %) genetic variant of unknown clinical significance, 1 (2.4 %) oncogenic fusion gene and 15 (36.6 %) deletions of the tumor suppressor genes.Conclusion. These findings point to the importance of molecular profiling of tumors for the optimal clinical care and development of new approaches to treatment aimed at molecular targets for personalized anticancer therapies.